ZxAKT1 is essential for K+ uptake and K+/Na+ homeostasis in the succulent xerophyte Zygophyllum xanthoxylum - Ma, Qing; Hu, Jing; Zhou, Xiang‐Rui; Yuan, Hui‐Jun; Kumar, Tanweer; Luan, Sheng; Wang, Suo‐Min (The Plant journal : for cell and molecular biology, 2017)
Summary The inward‐rectifying K+ channel AKT1 constitutes an important pathway for K+ acquisition in plant roots. In glycophytes, excessive accumulation of Na+ is accompanied by K+ deficiency under salt stress. However, in the succulent xerophyte Zygophyllum xanthoxylum, which exhibits excellent adaptability to adverse environments, K+ concentration remains at a relatively constant level despite increased levels of Na+ under salinity and drought conditions. In this study, the contribution of ZxAKT1 to maintaining K+ and Na+ homeostasis in Z. xanthoxylum was investigated. Expression of ZxAKT1 rescued the K+‐uptake‐defective phenotype of yeast strain CY162, suppressed the salt‐sensitive phenotype of yeast strain G19, and complemented the low‐K+‐sensitive phenotype of Arabidopsis akt1 mutant, indicating that ZxAKT1 functions as an inward‐rectifying K+ channel. ZxAKT1 was predominantly expressed in roots, and was induced under high concentrations of either KCl or NaCl. By using RNA interference technique, we found that ZxAKT1‐silenced plants exhibited stunted growth compared to wild‐type Z. xanthoxylum. Further experiments showed that ZxAKT1‐silenced plants exhibited a significant decline in net uptake of K+ and Na+, resulting in decreased concentrations of K+ and Na+, as compared to wild‐type Z. xanthoxylum grown under 50 mm NaCl. Compared with wild‐type, the expression levels of genes encoding several transporters/channels related to K+/Na+ homeostasis, including ZxSKOR, ZxNHX, ZxSOS1 and ZxHKT1;1, were reduced in various tissues of a ZxAKT1‐silenced line. These findings suggest that ZxAKT1 not only plays a crucial role in K+ uptake but also functions in modulating Na+ uptake and transport systems in Z. xanthoxylum, thereby affecting its normal growth. Significance Statement Succulent plants can better adapt to drought and salinity. Here we show that an inward‐rectifying potassium channel (ZxAKT1) contributes to this adaptation in Z. xanthoxylum, as unlike in glycophytes, where excessive accumulation of Na+ is accompanied by K+ deficiency under salt stress, in succulents K+ was maintained at a relatively constant level, despite increased Na+. Thus ZxAKT1 not only plays a crucial role in K+ uptake but also functions in modulating Na+ uptake and transport systems.